Pengaruh Social Media Marketing Melalui Aplikasi Twitter dan Weverse Terhadap Purchase Intention dan Brand Loyalty: Studi Kasus pada Pembelian Album Fisik Kpop Boygroup Treasure - Aklin Nindya Patricy; Saputri, Marheni Eka (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The K-Pop entertainment industry is experiencing fiercer competition due to the rapid development of the genre, which has been aided by technological advancements. Due to its large population, particularly among teens and young adults, Indonesia is the primary target market. YG Entertainment's Treasure, a 10-members South Korean boy band, came in fourth place among its rivals in terms of album sales. The purpose of this study is to identify how far the influence of social media marketing through the Twitter and Weverse applications on purchase intention and brand loyalty in purchasing Treasure boy group albums. The research method used is quantitative with a descriptive approach, using non-probability sampling techniques with a total of 385 respondents. Data collection was done by distributing questionnaires to Treasure fans in Indonesia. Data analysis was carried out using the SEM-PLS method with the help of the SmartPLS 4.1 software application. The results showed that social media marketing has a positive and significant impact on brand loyalty with a to value of 3.957 > ta value of 1.649. In addition, social media marketing has a positive and significant influence on purchase intention, and purchase intention has a positive and significant influence on brand loyalty. This research shows that social media marketing has a positive and significant effect on brand loyalty through the intervening variable of purchase intention in the case study of purchasing Treasure boy group physical albums.